A history of the Islamic world - Hill, Fred James; Awde, Nicholas (New York : Hippocrene Books, 2003)
A compact history introduces Islamic civilization, outlining developments from Islam's beginnings in seventh-century Arabia to the present day.
The rise of Islam. Cradle of Islam ; The Arab conquests and the age of empire ; The Abbasids and the rise of Baghdad ; Al-Andalus: Islam in Spain ; The mysticism of the Sufis ; The Crusades ; From Mongols to Mamluks ; Islam on the periphery: travels in Africa and Asia --
The age of the three great Muslim empires. The Ottomans ; The Safavids and Shi'ism: Persia reunified ; The Mughals in India --
Islam in the twentieth and twenty-first centuries. Creation of the nation-states ; Islam and the West: facing difficult times ; Afterword. The challenge of the future --
Key dates in Islamic history ; Key figures and dynasties in Islamic history ; Glossary of Islamic terms.
Includes index.
ENH
Karim International
Keywords: Islamic civilization; Islam -- 20th century; English language; Islamic countries -- History